Government policy, strategies of negotiation and the politics of protest in early seventeenth-century Ireland - Carroll, Stephen (Trinity College (Dublin, Ireland). Department of History, 2013)
The aim of this study is to provide an analysis of the reaction of Irish Catholics to government policy from the accession of James I in 1603 to the arrival of Thomas Wentworth in 1633. During this period the Dublin administration pursued aggressive reforms that aimed to alter the Irish polity in the aftermath of war. A succession of lords deputy and lord justices sought to 'civilise' the kingdom from its former 'barbarity', seeking to secure the country in the interests of New English Protestants. The overarching aim of this reform was to integrate Ireland more fully to practices in England.
Keywords: Histories & Humanities, Ph.D.; Ph.D. Trinity College Dublin.